Antibacterial composite material as well as preparation method and application thereof

By spraying bacteriostatic lotion onto the base cloth and through heat treatment, a stable complex was formed, and the platinum ions were successfully introduced to prepare a bacteriostatic composite material with high stability, lasting antibacterial properties and good biocompatibility. The problem of stability of traditional bacteriostatic materials and insufficient antibacterial effects is suitable for clean environmental protection fields.

CN119352289APending Publication Date: 2025-01-24FUTAI CLEAN TECH KUNSHAN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411614878.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Traditional antibacterial materials have shortcomings in their stability and antibacterial effects, and it is difficult to meet the clean industry's demand for high stability and long-lasting antibacterial performance.

Method used

By spraying bacteriostatic lotion onto the base cloth and through heat treatment, a stable complex was formed, and the platinum ions were successfully introduced to prepare a bacteriostatic composite material with high stability, lasting antibacterial performance and good biocompatibility.

Benefits of technology

It achieves high stability, long-lasting antibacterial performance and good biocompatibility of antibacterial composite materials. It is suitable for biopharmaceuticals, medical clean engineering and food processing and other fields, and significantly improves the safety performance in the clean and environmental protection field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005131916630000081
    Figure BDA0005131916630000081
  • Figure BDA0005131916630000091
    Figure BDA0005131916630000091
Patent Text Reader

Abstract

The invention provides a bacteriostatic composite material as well as a preparation method and application thereof, the bacteriostatic composite material is obtained by spraying a bacteriostatic emulsion onto base cloth and performing heat treatment, and the bacteriostatic emulsion comprises a specific amount of matrix, a platinum catalyst, a dispersing agent and water; the components contained in the antibacterial emulsion are limited, so that the base cloth and the antibacterial emulsion can form a stable complex through a chemical reaction, platinum ions are successfully introduced, and the obtained antibacterial composite material has high stability, lasting antibacterial performance and good biocompatibility; and the composite material has high antibacterial activity and broad-spectrum antibacterial effect, can be used as a filtering material, and is widely applied to the clean and environment-friendly fields of biological pharmacy, medical places, food processing occasions and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of filtration technology, and specifically relates to an antibacterial composite material and a preparation method and application thereof. Background Art

[0002] As people pay more and more attention to health and hygiene, the demand for clean industry is also increasing. In the fields of biopharmaceuticals, medical clean engineering, food processing and semiconductor manufacturing, various filters, purifiers and other equipment are needed to ensure the cleanliness of the production environment. However, traditional filter materials often have problems such as poor sterilization effect and susceptibility to contamination. Therefore, it is of great significance to develop a new antibacterial composite material to ensure the sterilization effect and service life of the filter.

[0003] At present, the antibacterial materials on the market are mainly metal ion type, photocatalyst type and nanomaterial type, etc. Among them, metal ion type antibacterial materials have high antibacterial activity and broad-spectrum antibacterial effect, but the stability of metal ions is poor and they are easy to react with acids, alkalis and other chemicals in the environment, resulting in decreased antibacterial stability.

[0004] Therefore, in view of the above technical problems, how to develop an antibacterial composite material with excellent and lasting antibacterial properties is still a technical problem that urgently needs to be solved in this field. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an antibacterial composite material and a preparation method and application thereof. The antibacterial composite material has high stability, lasting antibacterial properties and good biocompatibility, as well as high antibacterial activity and a broad-spectrum antibacterial effect, which solves the problem of lack of antibacterial materials in the clean industry. To a certain extent, it also greatly guarantees the safety performance of personnel and products in the clean industry, especially in some biopharmaceuticals, medical clean engineering and food production occasions.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides an antibacterial composite material, wherein the antibacterial composite material is obtained by spraying an antibacterial emulsion onto a base fabric and subjecting the base fabric to heat treatment.

[0008] Taking the total mass as 100%, the dosage of each component contained in the antibacterial emulsion is as follows:

[0009] Matrix 40-80%;

[0010] Platinum catalyst 0.2-8%;

[0011] Dispersant 0.2-4%;

[0012] The balance is water.

[0013] The antibacterial composite material provided by the present invention is obtained by spraying an antibacterial emulsion onto a base fabric and subjecting it to heat treatment, and the antibacterial emulsion contains a specific amount of a matrix, a platinum catalyst, a dispersant and water; by limiting the components contained in the antibacterial emulsion, the base fabric can form a stable complex with the antibacterial emulsion through a chemical reaction, and platinum ions are successfully introduced, so that the obtained antibacterial composite material has high stability, lasting antibacterial performance and good biocompatibility, and also has high antibacterial activity and a broad-spectrum antibacterial effect, and can be used as a filter material and widely used in clean and environmentally friendly fields such as biopharmaceuticals, medical places, and food processing occasions.

[0014] Specifically, on the one hand, since the antibacterial emulsion contains a platinum catalyst, the platinum catalyst can cause water molecules to produce hydrogen oxide and active hydrogen. These active oxides have extremely strong oxidizing properties and can destroy bacterial cell walls and viral proteins, leading to the death of microorganisms; and, the platinum catalyst can polarize water molecules and decompose them into hydrogen and oxygen. The polarized water molecules form negative ion hydroxyl radicals (OH-) in the electrolyte solution, which have strong bactericidal ability and further destroy the cell structure of bacteria; in addition, the process can also produce ozone, which has a strong oxidizing effect on bacteria, viruses and fungi, and can destroy their cell structure and DNA to achieve a killing effect; on the other hand, the platinum catalyst can form coordination bonds with oxygen atoms in silicon dioxide, the main material of the base fabric, to form a platinum silicate complex, and then have a stable chemical structure, so that the obtained antibacterial composite material has high antibacterial activity and a broad-spectrum antibacterial effect without affecting the filtration efficiency, and also has good biocompatibility.

[0015] The dosage of the matrix may be 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%, etc.

[0016] The amount of the platinum catalyst can be 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7% or 8%, etc.

[0017] The dispersant may be 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5% or 4%, etc.

[0018] Preferably, the base fabric is ultra-fine glass fiber fabric.

[0019] Preferably, the thickness of the ultrafine glass fiber cloth is 0.3-0.6 mm, for example, 0.3 mm, 0.35 mm, 0.4 mm, 0.45 mm, 0.5 mm, 0.55 mm or 0.6 mm.

[0020] Preferably, based on the mass of the base fabric being 1 kg, the amount of the antibacterial emulsion used is 15 to 20 g, for example, 15 g, 15.5 g, 16 g, 16.5 g, 17 g, 17.5 g, 18 g, 18.5 g, 19 g, 19.5 g or 20 g, etc.

[0021] Preferably, the matrix comprises any one of metal, nanocomposite material or metal oxide photocatalytic material or a combination of at least two thereof.

[0022] Preferably, the metal includes any one of silver powder, copper powder or zinc powder, or a combination of at least two of them.

[0023] Among them, the silver powder has strong antibacterial properties and can destroy bacterial cell membranes by releasing Ag ions, leading to bacterial death; the copper powder can release Cu ions to destroy bacterial metabolic pathways and inhibit their growth and reproduction; the zinc powder destroys bacterial cell walls and cell membranes to make them inactive; all have excellent antibacterial properties.

[0024] Preferably, the nanocomposite material comprises silver-platinum composite nanomaterial.

[0025] Among them, both silver and platinum in the silver-platinum composite nanomaterial have excellent antibacterial properties. Silver can destroy bacterial cell membranes by releasing Ag ions, leading to bacterial death; platinum can further enhance the antibacterial activity of the composite material due to its catalytic properties. The combination of the two can exert a synergistic effect, produce an inhibitory effect on a variety of bacteria, viruses and fungi, and achieve broad-spectrum antibacterial effects.

[0026] Preferably, the metal oxide photocatalytic material comprises titanium dioxide and / or zinc oxide.

[0027] Among them, the titanium dioxide can produce strong oxidizing hydroxyl radicals and superoxide anions under light conditions. These active substances can effectively decompose organic pollutants, kill bacteria and viruses, and have self-cleaning and antibacterial properties; the zinc oxide is also a photocatalytic material, which can produce electron-hole pairs under light, and then produce strong oxidizing free radicals for degrading organic matter and inactivating microorganisms. The active oxygen species produced by these two metal oxides under photocatalysis can effectively destroy the cell walls of bacteria and the protein shells of viruses, thereby achieving an antibacterial effect.

[0028] Preferably, the platinum catalyst comprises a Custer platinum catalyst.

[0029] In the present invention, the Custer platinum catalyst is a commercially available high-activity platinum catalyst that can maintain stability under a variety of environments and is not easily deactivated, which enables the antibacterial composite material to maintain its performance under different conditions, prolongs its service life, and reduces the frequency of replacement.

[0030] Preferably, the dispersant includes any one of polyethylene sulfonate, stearate, lignin sulfonate or tea saponin, or a combination of at least two thereof.

[0031] Preferably, the antibacterial agent further comprises any one of a stabilizer, a toughening agent or a lubricant, or a combination of at least two thereof.

[0032] Preferably, the stabilizer includes polyol compounds such as glycerol and propylene glycol, which can maintain the stability of the system by adjusting the osmotic pressure of the emulsion.

[0033] Preferably, the toughening agent includes carboxymethyl cellulose (CMC), hydroxyethyl cellulose (HEC), etc. These substances can form a grid structure in water, thereby improving the cohesion and consistency of the emulsion.

[0034] Preferably, the lubricant includes stearic acid, palmitic acid, glyceride or fatty acid methyl ester, etc. These substances can improve the processing performance of the material and the surface quality of the finished product.

[0035] In a second aspect, the present invention provides a method for preparing the antibacterial composite material as described in the first aspect, the preparation method comprising the following steps:

[0036] (1) mixing a substrate, a platinum catalyst, a dispersant and water to obtain an antibacterial emulsion;

[0037] (2) Spraying the antibacterial emulsion obtained in step (1) onto the base fabric, and subjecting the base fabric to heat treatment to obtain the antibacterial composite material.

[0038] Preferably, based on the mass of the base fabric being 1 kg, the amount of the antibacterial emulsion used is 15 to 20 g, for example, 15 g, 15.5 g, 16 g, 16.5 g, 17 g, 17.5 g, 18 g, 18.5 g, 19 g, 19.5 g or 20 g, etc.

[0039] Preferably, the temperature of the heat treatment is 70-90°C, for example, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C or 90°C.

[0040] Preferably, the heat treatment time is 40 to 80 min, for example, 40 min, 45 min, 50 min, 55 min, 60 min, 65 min, 70 min, 75 min or 80 min.

[0041] In a third aspect, the present invention provides a use of the antibacterial composite material as described in the first aspect as a filter material.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] The antibacterial composite material provided by the present invention is obtained by spraying an antibacterial emulsion onto a base fabric and subjecting it to heat treatment, and the antibacterial emulsion contains a specific amount of a matrix, a platinum catalyst, a dispersant and water; by limiting the components contained in the antibacterial emulsion, the base fabric can form a stable complex with the antibacterial emulsion through a chemical reaction, and platinum ions are successfully introduced, so that the obtained antibacterial composite material has high stability, lasting antibacterial performance and good biocompatibility, and also has high antibacterial activity and a broad-spectrum antibacterial effect, and can be used as a filter material and widely used in clean and environmentally friendly fields such as biopharmaceuticals, medical places, and food processing occasions. DETAILED DESCRIPTION

[0044] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0045] Unless otherwise specified, the raw materials involved in the following specific embodiments are all conventional materials in the art and can be purchased from commercial products.

[0046] Example 1

[0047] An antibacterial composite material, the preparation method of which comprises the following steps:

[0048] (1) 50 wt% silver powder (D 50 The particle size is 20 nm), 5wt% of Custer platinum catalyst, 2wt% of sodium lignin sulfonate, 1wt% of glycerol, 2wt% of carboxymethyl cellulose and 40wt% of deionized water are mixed evenly to obtain an antibacterial emulsion;

[0049] (2) Spraying the antibacterial emulsion obtained in step (1) onto an ultra-fine glass fiber base cloth with a thickness of 0.5 mm, with the mass of the ultra-fine glass fiber base cloth being 1 kg and the amount of the antibacterial emulsion being 18 g, and then heat-treating the ultra-fine glass fiber base cloth at 80° C. for 60 min to obtain the antibacterial composite material.

[0050] Example 2

[0051] An antibacterial composite material, the preparation method of which comprises the following steps:

[0052] (1) 70 wt % of silver-platinum composite nanomaterial (silver-platinum atomic ratio is 1:10), 6 wt % of Custer platinum catalyst, 2 wt % of tea saponin, 1 wt % of glycerol, 1 wt % of carboxymethyl cellulose and 20 wt % of deionized water are uniformly mixed to obtain an antibacterial emulsion;

[0053] (2) Spraying the antibacterial emulsion obtained in step (1) onto an ultra-fine glass fiber base cloth with a thickness of 0.5 mm, with the mass of the ultra-fine glass fiber base cloth being 1 kg and the amount of the antibacterial emulsion being 17 g, and heat treating the mixture at 70° C. for 80 min to obtain the antibacterial composite material.

[0054] Example 3

[0055] An antibacterial composite material, the preparation method of which comprises the following steps:

[0056] (1) 45 wt% titanium dioxide (D 50 The particle size is 20 nm), 7wt% of Custer platinum catalyst, 2wt% of sodium stearate, 1wt% of glycerol, 1wt% of carboxymethyl cellulose and 44wt% of deionized water are mixed evenly to obtain an antibacterial emulsion;

[0057] (2) Spraying the antibacterial emulsion obtained in step (1) onto an ultra-fine glass fiber base cloth with a thickness of 0.5 mm, with the mass of the ultra-fine glass fiber base cloth being 1 kg and the amount of the antibacterial emulsion being 16 g, and heat treating the mixture at 90° C. for 40 min to obtain the antibacterial composite material.

[0058] Example 4

[0059] An antibacterial composite material, which differs from Example 1 in that D 50 Copper powder with a particle size of 20nm replaces D 50 The silver powder has a particle size of 20 nm, and other materials, amounts and preparation methods are the same as those in Example 1.

[0060] Example 5

[0061] An antibacterial composite material, which differs from Example 1 in that D 50 Zinc powder with a particle size of 20 nm replaces D 50 The silver powder has a particle size of 20 nm, and other materials, amounts and preparation methods are the same as those in Example 1.

[0062] Example 6

[0063] An antibacterial composite material, which differs from Example 1 in that, based on the mass of the ultrafine glass fiber base cloth being 1 kg, the amount of the antibacterial emulsion used is 15 g, and other materials, amounts used and preparation methods are the same as those in Example 1.

[0064] Example 7

[0065] An antibacterial composite material, which differs from Example 1 in that, based on the mass of the fine glass fiber base cloth being 1 kg, the amount of the antibacterial emulsion used is 20 g, and other materials, amounts used and preparation methods are the same as those in Example 1.

[0066] Example 8

[0067] An antibacterial composite material, which differs from Example 1 in that, based on the mass of the ultrafine glass fiber base cloth being 1 kg, the amount of the antibacterial emulsion used is 14 g, and other materials, amounts used and preparation methods are the same as those in Example 1.

[0068] Comparative Example 1

[0069] An ultra-fine glass fiber base cloth with a thickness of 0.5mm.

[0070] Comparative Example 2

[0071] An antibacterial composite material, which differs from Example 1 in that the mass proportion of silver powder is 30wt%, the usage of deionized water is 60wt%, and other materials, usage and preparation methods are the same as those in Example 1.

[0072] Comparative Example 3

[0073] An antibacterial composite material, which differs from Example 1 in that no Custer platinum catalyst is added, the amount of deionized water used accounts for 45wt%, and other materials, amounts used and preparation methods are the same as those in Example 1.

[0074] Performance Test:

[0075] According to the evaluation regulations of GB / T 20944.2-2007 on the antibacterial properties of textiles, the antibacterial composite materials obtained in Examples 1-8 and Comparative Examples 1-3 were tested for performance. When the antibacterial value was ≥1 or the antibacterial rate was ≥90.00%, the sample had an antibacterial effect; when the antibacterial value was ≥2 or the antibacterial rate was ≥99.00%, the sample had a good antibacterial effect. The relevant test results are shown in Table 1 below.

[0076] Table 1

[0077]

[0078]

[0079] It can be seen that the antibacterial composite material provided by the present invention is obtained by spraying the antibacterial emulsion onto the base fabric and subjecting it to heat treatment, and the antibacterial emulsion contains a specific amount of a matrix, a platinum catalyst, a dispersant and water; by limiting the components contained in the antibacterial emulsion, the base fabric can form a stable complex with the antibacterial emulsion through a chemical reaction, and platinum ions are successfully introduced, so that the obtained antibacterial composite material has high stability, lasting antibacterial performance and good biocompatibility, and also has high antibacterial activity and a broad-spectrum antibacterial effect, and can be used as a filter material and widely used in clean and environmentally friendly fields such as biopharmaceuticals, medical places, and food processing occasions.

[0080] The applicant declares that the present invention illustrates an antibacterial composite material and its preparation method and application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An antibacterial composite material, characterized in that: The antibacterial composite material is obtained by spraying the antibacterial emulsion onto the base fabric and subjecting the base fabric to heat treatment; Taking the total mass as 100%, the dosage of each component contained in the antibacterial emulsion is as follows: Matrix 40-80%; Platinum catalyst 0.2-8%; Dispersant 0.2-4%; The balance is water.

2. The antibacterial composite material according to claim 1, characterized in that: The base fabric is ultra-fine glass fiber fabric; Preferably, the thickness of the ultra-fine glass fiber cloth is 0.3-0.6 mm; Preferably, based on 1 kg of the base fabric, the amount of the antibacterial emulsion used is 15 to 20 g.

3. The antibacterial composite material according to claim 1 or 2, characterized in that: The matrix comprises any one or a combination of at least two of a metal, a nanocomposite material or a metal oxide photocatalytic material; Preferably, the metal includes any one of silver powder, copper powder or zinc powder, or a combination of at least two thereof; Preferably, the nanocomposite material comprises a silver-platinum composite nanomaterial; Preferably, the metal oxide photocatalytic material comprises titanium dioxide and / or zinc oxide.

4. The antibacterial composite material according to any one of claims 1 to 3, characterized in that: The platinum catalyst includes a Custer platinum catalyst.

5. The antibacterial composite material according to any one of claims 1 to 4, characterized in that: The dispersant includes any one of polyethylene sulfonate, stearate, lignin sulfonate or tea saponin, or a combination of at least two of them.

6. The antibacterial composite material according to any one of claims 1 to 5, characterized in that: The antibacterial emulsion further comprises any one of a stabilizer, a toughening agent or a lubricant or a combination of at least two of them.

7. A method for preparing the antibacterial composite material according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) mixing a substrate, a platinum catalyst, a dispersant and water to obtain an antibacterial emulsion; (2) Spraying the antibacterial emulsion obtained in step (1) onto the base fabric, and subjecting the base fabric to heat treatment to obtain the antibacterial composite material.

8. The preparation method according to claim 7, characterized in that: Based on the mass of the base fabric being 1 kg, the amount of the antibacterial emulsion used is 15 to 20 g.

9. The preparation method according to claim 7 or 8, characterized in that: The heat treatment temperature is 70-90° C. and the time is 40-80 min.

10. Use of the antibacterial composite material according to any one of claims 1 to 6 as a filter material.